2015
DOI: 10.4166/kjg.2015.65.4.222
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Resolution of Eosinophilic Liver Abscess Associated with Toxocariasis by Albendazole Treatment

Abstract: Background/Aims: Visceral larva migrans, caused by Toxocara canis and Toxocara cati, has emerged as a significant cause of eosinophilic liver abscess (ELA). Differentiation of ELA associated with toxocariasis (ELA-T) from metastasis or primary liver malignancy is sometimes difficult. However, the role of albendazole treatment remains uncertain in this condition. The aim of this study was to evaluate whether albendazole can enhance the radiologic resolution of ELA-T. Methods: We retrospectively reviewed the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…US changes can last for 2 years or more. In rare cases, phlegmonous inflammation and abscess formation require biopsy and histological evaluation to exclude liver metastases and other inflammatory conditions including the "pseudo-inflammatory liver tumor" [60], which demonstrates abundant eosinophilic (granulomatous) infiltration and abscess formation.…”
Section: Livermentioning
confidence: 99%
See 1 more Smart Citation
“…US changes can last for 2 years or more. In rare cases, phlegmonous inflammation and abscess formation require biopsy and histological evaluation to exclude liver metastases and other inflammatory conditions including the "pseudo-inflammatory liver tumor" [60], which demonstrates abundant eosinophilic (granulomatous) infiltration and abscess formation.…”
Section: Livermentioning
confidence: 99%
“…Previous studies demonstrated radiologic resolution of eosinophilic liver abscess associated with toxocariasis can be accelerated with albendazole treatment. Hence, the inconvenience associated with long-term follow-up and unnecessary concerns from patients can be eliminated with albendazole treatment [60].…”
Section: Livermentioning
confidence: 99%
“…Các biểu hiện trên da là một trong những triệu chứng thường gặp ở bệnh giun đũa chó, mèo và trong một số trường hợp, những biểu hiện này là dấu hiệu duy nhất. Theo một số nghiên cứu tổn thương da trong toxocariasis thường gặp là ngứa, ban, mày đay mãn tính, phù mạch (angioedema), eczéma, tổ đỉa (dyshidrosis) đôi khi là viêm mạch (vasculitis), hội chứng Reiter, hội chứng Well, viêm nang lông tăng bạch cầu ái toan (eosinophilic folliculitis)[12]. Tỷ lệ mày đay mãn cao trong số các triệu chứng tổn thương da phù hợp với một số nghiên cứu khác.…”
unclassified